ПРОФЕСІЙНА ПІДГОТОВКА ПЕДАГОГА ДО ОРГАНІЗАЦІЇ ДОСЛІДНИЦЬКОЇ ДІЯЛЬНОСТІ В НАВЧАЛЬНОМУ ПРОЦЕСІ (Педагогіка вищої та середньої школи, 2009)
The article deals with the theoretical foundations of problem of preparation of teacher to the organisation of the research activity in the educational process. The article ground importance and peculiarity of usage of the research methods in the educational and upbringing process.